Influence of prerequisite concepts understanding and mathematical communication skills toward student’s mathematical proving ability - Salsabila, Ellis (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2019)
This study aims to describe the influence of prerequisite concepts understanding and mathematical communication skills on the mathematical proving ability of Mathematics Education Program students in the Faculty of Mathematics and Science, State University of Jakarta (FMIPA UNJ). The method used in this study was a survey and correlational techniques. The study population was all students of the Mathematics Education Program FMIPA UNJ in 2018. The study sample was taken with a simple random sampling technique, there were 50 students in total. In this study, the dependent variable was mathematical proving ability (Y) and the independent variables were the prerequisite concepts understanding (X1) and mathematical communication skills (X2). This study based on the inferential statistical analysis of research data by using multiple regression analyses to test the effect of independent variables on the dependent variables. The results obtained were: 1) the prerequisite concepts understanding had a positive effect and significant on students’ mathematical proving ability, 2) mathematical communication skills had a positive effect and significant on students’ mathematical proving ability, and 3) prerequisite concepts understanding and mathematical communication skills simultaneously had a positive effect and significant on mathematical proving ability with effect size of 69.3%. Pengaruh pemahaman prerequisite concepts dan kemampuan komunikasi matematis terhadap mathematical proving ability mahasiswa Abstrak Penelitian ini bertujuan untuk memperoleh informasi tentang pengaruh pemahaman prerequisite concepts dan kemampuan komunikasi matematis terhadap kemampuan membuktikan matematis mahasiswa Pendidikan Matematika di Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Jakarta (FMIPA UNJ). Metode yang digunakan dalam penelitian ini adalah metode survei dan teknik korelasional. Populasi penelitian adalah seluruh mahasiswa Program Studi Pendidikan Matematika FMIPA UNJ tahun 2018. Sampel penelitian diambil dengan teknik simple random sampling sebanyak 50 mahasiswa. Variabel terikat dalam penelitian ini adalah kemampuan membuktikan matematis (Y) dan variabel bebasnya adalah pemahaman prerequisite concepts (X1) dan kemampuan komunikasi matematis (X2). Penelitian ini berdasarkan analisis statistik inferensial atas data penelitian dengan menggunakan analisis regresi ganda untuk menguji pengaruh variable-variabel bebas terhadap variabel terikat. Hasil yang diperoleh adalah: 1) pemahaman prerequisite concepts berpengaruh positif dan signifikan terhadap kemampuan pembuktian matematis mahasiswa, 2) kemampuan komunikasi matematis berpengaruh positif dan signifikan terhadap kemampuan pembuktian matematis mahasiswa, 3) pemahaman prerequisite concepts dan kemampuan komunikasi matematis secara bersama-sama (simultan) memberikan pengaruh positif dan signifikan terhadap kemampuan pembuktian matematis mahasiswa dengan besar pengaruh sebesar 69,3%.